Quantum Teaching-Learning Model Assisted Audiovisual Media on The Ability of Students' Science Competencies - Sumasningtyas, Ni Luh Regita; Manuaba, I B Surya; Kristiantari, Maria Goreti Rini (International Journal of Elementary Education, 2020)
The competence of scientific knowledge which is still low due to the learning process used is less innovative, which affects students' interest in learning with reduced interest in learning that will affect learning outcomes. Thus, research was carried out to examine the effect of the Quantum Teaching-learning model assisted by Audio Visual media on science knowledge competencies. This type of research is a quasi-experimental design using the Nonequivalent Control Group Design. The population of this study was all class IV SDN as many as 191. The sampling technique in this study used a random sampling technique with a sample of the experimental group as many as 34 students and the control class as many as 36 students. The instrument used to collect data was a science knowledge competency test. Science knowledge competency data were analyzed by t-test. Based on the results of t-test analysis, it was obtained count = 3.71 and at a significance level of 5% with dk = 34 + 36 - 2 = 68, it was obtained t table = 1.67. The results of the analysis show that t = 3.71> t table 1.67, then H0 is rejected. Thus, there is a significant difference in the competence of science knowledge between groups of students who are taught using the Quantum Teaching model assisted by audio-visual media and groups of students who are taught using conventional learning.